Enhancing Organizational Control Through Business Intelligence: Monitoring and Automated Alerts - Hasdi Putra; Raidha Qatrunnada; Jefril Rahmadoni; Fajrul Khairati (Electronic Journal of Education, Social Economics and Technology, 2025)
This study explores the role of Business Intelligence (BI) systems in enhancing organizational control through real-time monitoring, automated alerts, and predictive analytics. By integrating a BI system into operational workflows, this research demonstrates significant improvements in efficiency, decision-making, and responsiveness to emerging challenges. Real-time dashboards enabled stakeholders to monitor key performance indicators (KPIs), such as export volumes, commodity values, and transaction frequencies, providing immediate insights for proactive management. The automated alert system reduced anomaly response times by 42%, enabling timely corrective actions and minimizing operational disruptions. Additionally, the predictive analytics module achieved a 92% accuracy rate in forecasting trends, allowing for better resource allocation and strategic planning. Stakeholder feedback highlighted the system's usability, relevance, and operational impact, with 80% of users reporting enhanced decision-making capabilities and 75% noting increased efficiency in their daily tasks. This study provides a replicable framework for implementing BI systems to support real-time decision-making and improve operational control. While the findings are based on a specific context, they underscore the scalability of BI systems across different sectors and organizational settings. Future research should investigate the long-term impacts of BI systems, explore their integration with emerging technologies such as artificial intelligence, and address challenges related to data quality and user adoption. This research positions BI systems as indispensable tools for fostering agility, efficiency, and strategic alignment in dynamic operational environments.